2020
DOI: 10.1002/1873-3468.13725
|View full text |Cite
|
Sign up to set email alerts
|

Zinc transporters maintain longevity by influencing insulin/IGF‐1 activity in Caenorhabditis elegans

Abstract: Adequate dietary intake of essential metals such as zinc is important for maintaining homeostasis. Abnormal zinc intake in Caenorhabditis elegans has been shown to increase or decrease normal lifespan by influencing the insulin/ IGF-1 pathway. Distribution of zinc is achieved by a family of highly conserved zinc transport proteins (ZIPT in C. elegans). This study investigated the role of the zipt family of genes and showed that depletion of individual zipt genes results in a decreased lifespan. Moreover, zipt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In addition, four (sic-2, acr-10, nca-2, and EVM0006162) out of five genes enriched in "ion transmembrane transporter activity" in 60‰ vs. 30‰ also had elongated 3 ′ UTRs despite the other one gene, zipt-16, having a shortened 3 ′ UTR. As expected, zipt-16 was also a significantly upregulated gene in 60‰ vs. 30‰ salinity (Supplementary Table S1), and has been reported to have interactions with daf-16 and skn-1 [59]. The two transcripts of zipt-16 (EVM0008784.1 and EVM0008784.2) were also significantly upregulated in 60‰ vs. 30‰ salinity (Supplementary Table S22).…”
Section: The Marine Nematode Exhibits Distinct Apa Usage Under Differ...supporting
confidence: 69%
“…In addition, four (sic-2, acr-10, nca-2, and EVM0006162) out of five genes enriched in "ion transmembrane transporter activity" in 60‰ vs. 30‰ also had elongated 3 ′ UTRs despite the other one gene, zipt-16, having a shortened 3 ′ UTR. As expected, zipt-16 was also a significantly upregulated gene in 60‰ vs. 30‰ salinity (Supplementary Table S1), and has been reported to have interactions with daf-16 and skn-1 [59]. The two transcripts of zipt-16 (EVM0008784.1 and EVM0008784.2) were also significantly upregulated in 60‰ vs. 30‰ salinity (Supplementary Table S22).…”
Section: The Marine Nematode Exhibits Distinct Apa Usage Under Differ...supporting
confidence: 69%
“…Furthermore, NBMI has the potential to chelate cellular metal ions with high affinity for free sulfhydryl groups such as Zn 2+ , which play important roles in the development of the animal [ [31] , [32] , [33] ]. Studies have shown that reducing Zn 2+ levels promotes nuclear localization of DAF-16 [ 32 , 34 ]. The interactive effects of NBMI and Zn 2+ in C. elegans deserve further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, zinc supplementation was shown to decrease markers of oxidative stress and the production of pro-inflammatory cytokines in elderly patients. However, surplus zinc supplementation induces senescence of several cell types and reduces lifespan in Caenorhabditis elegans [91,92]. Further in this section, we focus on recent publications investigating the role of zinc in ageing-related functional and structural changes in the cardiovascular system.…”
Section: Aged Heartmentioning
confidence: 99%
“…of pro-inflammatory cytokines in elderly patients. However, surplus zinc sup tion induces senescence of several cell types and reduces lifespan in Caenorhab [91,92]. Further in this section, we focus on recent publications investigating zinc in ageing-related functional and structural changes in the cardiovascular It is known that some zinc transporters are upregulated by pro-inflammato such as IL-6 (interleukin 6), in an age-dependent manner.…”
Section: Aged Heartmentioning
confidence: 99%